1979
DOI: 10.1149/1.2129013
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies on Ionic Nitride Solutions in Molten Salts

Abstract: iodide can only be explained by assuming some solubility of foreign cations in the solid (K + or H + ). These ions can enter from the solution and seem to have a mobility (diffusion coefficient) in the solid comparable to that of the silver ions. Detailed data cannot be obtained from the present results; it seems worthwhile to study the solubility and diffusion coefficient of such foreign ions by more direct solid-state methods.The main difference between the behavior of the two compounds Ag3SI and Ag19115P~O7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The difference between experimentally observed, ⌬E decomp , and the ⌬E Li 3 N o ͑0.155 V at 900 K͒ was more than 140 mV, therefore, the a Li 3 N ͑s͒ is estimated to be lower than 4 ϫ 10 Ϫ3 . This is in reasonable accord with the work by Bonomi et al 2 and Goto et al 6 To measure ⌬E decomp with sufficient reliability, an alternative method using a Pb-Li alloy electrode was employed. Using the Pb-Li liquid alloy in equilibrium with molten salt under nitrogen atmosphere, it is possible to measure lithium metal activity in molten salt with respect to the Li/Li ϩ reference.…”
Section: Resultssupporting
confidence: 85%
“…The difference between experimentally observed, ⌬E decomp , and the ⌬E Li 3 N o ͑0.155 V at 900 K͒ was more than 140 mV, therefore, the a Li 3 N ͑s͒ is estimated to be lower than 4 ϫ 10 Ϫ3 . This is in reasonable accord with the work by Bonomi et al 2 and Goto et al 6 To measure ⌬E decomp with sufficient reliability, an alternative method using a Pb-Li alloy electrode was employed. Using the Pb-Li liquid alloy in equilibrium with molten salt under nitrogen atmosphere, it is possible to measure lithium metal activity in molten salt with respect to the Li/Li ϩ reference.…”
Section: Resultssupporting
confidence: 85%
“…The electrolytic formation of nitrides from N 2 in molten alkali chlorides was reported prior to 1980. 337,338 Moreover, in 1998, Goto et al 339 reported that N 2 molecules can be electrochemically reduced to nitride ions (1/2N 2 + 3e − → N 3− ) in the molten eutectic mixture of LiCl−KCl (operating at 450 °C) at a nickel wire electrode. Since then, Murakami et al carried out a series of electrochemical ammonia synthesis experiments in the molten eutectic mixture of LiCl−KCl− CsCl containing 0.5 mol % Li 3 N, using hydrogen gas (H 2 ), 340,341 methane (CH 4 ), 342 hydrogen sulfide (H 2 S), 343 hydrogen chloride (HCl), 344 or water (H 2 O) 345,346 as the hydrogen source.…”
Section: N 2 Electroreduction In Molten Alkali Chloridesmentioning
confidence: 99%
“…(12)],which themselves can be reduced [Eq. (13), (14)], presumably at the same potentials as c1 and c3, respectively. Theproduction of Hfrom NH 2À during a2/c2 explains why the current for the non-N based a3/c3 couple is of similar magnitude to the Nb ased processes.…”
Section: Voltammetric Analysis Of Redox Active Speciesmentioning
confidence: 99%
“…[7][8][9][10][11][12] In particular, it has been reported that molten LiCl, and related eutectics,p ossess the fascinating ability to stabilise the N 3À ion and establish the reversible N 2 /N 3À redox couple at ambient pressure. [13][14][15][16] Ito and co-workers proposed that this could be utilised in an ammonia synthesis process,by coupling the reduction of N 2 [Eq. (1)] at ac athode with its oxidation in the presence of H 2 [Eq.…”
Section: Introductionmentioning
confidence: 99%